Cross-Cultural Pastoral: The Practice of Indoor Grave Traditions - Lorameng, Sastrilya Asye; Mawuntu, Marhaeni Luciana (CV. Publikasi Indonesia, 2025)
The Sangihe tribe of North Sulawesi practices indoor graves as a hereditary tradition, perceived as natural and harmonious with daily life. Despite its cultural significance, this practice raises questions about its alignment with Christian teachings and modern norms. This study explores how the GMIST Getsemani Salurang congregation reconciles the tradition with faith, aiming to develop a cross-cultural pastoral model that respects local wisdom while fostering theological reflection. A qualitative case study approach was employed, with data collected through interviews with congregants (e.g., Inyong, 60; Andri, 72) and analysis of church practices. Thematic analysis was guided by Niebuhr’s